Strategi Pemasaran Garam Kusamba Dalam Upaya Meningkatkan Pendapatan Petani - Luh Putu Kirana Pratiwi; I Made Budiasa (Jurnal MeA (Media Agribisnis), 2023)
This study aims to determine internal factors, external factors, and alternative marketing strategies. The location of this research is in Kusamba Village, Dawan District, Klungkung Regency. Totaled respondents in this study were 38 people consisting of 20 Kusamba salt farmers and 18 external respondents (village government, Agriculture Service, Klungkung District Cooperative Office, salt sellers: stalls, shops, retailers, consumers). The analytical method in this study uses SWOT analysis. Based on the results of the study, identifying internal factors as the main strength is that Kusamba Salt has good quality and the main weakness factor is that product quality in the process of making Kusamba salt depends on climate. While the external factor which is the main opportunity is the existence of equipment assistance from the government and the factor which is a threat is that similar competitors are superior in following market trends quickly. Furthermore, an alternative marketing strategy for Kusamba salt to increase farmers' income is in quadrant 1, which means that the strategy that can be used in this quadrant is to grow and develop, support aggressive growth policies through the implementation of Strength Opportunities strategies, including: a) Utilizing technological support and government branding in increasing product superiority, and b) Making the Kumba salt farming business an educational tour